Eliminace zápachu na stokové síti - Novotný, Jiří (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Diplomová práce je zaměřena na eliminaci zápachu ve stokovém systému. V práci je obsažena rešerše problematiky vzniku, kontroly a nebezpečí sulfanu pro člověka a stokový systém. Dále jsou popsány metody odstranění sulfanu z vody, ze vzduchu a podrobně jsou popsány vybrané sorbenty. Praktická část se zabývá testováním sorbentů na odstranění sulfanu v laboratorním prostředí. V praktické části je také řešen zápach na konkrétním území pomocí sorpce na kanalizačních filtrech. Z měřených dat a z výsledků laboratorních rozborů jsou vyhodnoceny souvislosti vzniku zápachu a je uvedeno doporučení pro provozovatele.

The diploma thesis focusses on the elimination of odor in the sewer system. Firstly, the paper contains the research in problematics of the origin, control and risks of the hydrogen sulfide for humans as well as for the sewer system. Secondly, the paper describes methods for hydrogen sulfide removal from water, air and in addition to that the selected sorbents are described in detail. Practical part deals with sorbent testing for hydrogen sulfide removal in laboratory environment. The practical part also follows up the odor in the particular area through sorption on sewer filters. From the measured data and from the results of the laboratory analyzes the consequences of the odor are evaluated and recommendations for the operator are presented.
Eliminating odors in the sewer network
Keywords: Zápach; sulfan; sorbenty; filtrace; kanalizace; sorpce; Odor; hydrogen sulfide; sorbents; filtration; sewer system; sorption